Efficacy, Safety, and Retreatment Benefit of Micropulse Transscleral Cyclophotocoagulation in Glaucoma. Issue 9 (15th September 2021) - Chamard, Chloé; Bachouchi, Alex; Daien, Vincent; Villain, Max
Abstract : Precis: Micropulse transscleral cyclophotocoagulation (MP-TSCPC) with a 120-second setting reduces intraocular pressure (IOP) with a 6-month success of 45.5%. Only late (>6 mo) failure seem to present a benefit for retreatment. Purpose: The purpose of this study was to assess MP-TSCPC efficacy, safety, factors of success, and retreatment benefit in open-angle glaucoma. Patients and Methods: A retrospective consecutive case series study. We included patients with open-angle glaucoma who were naive of a cycloablative procedure and underwent MP-TSCPC at 2000 mW for 120 seconds between May 1, 2017, and October 31, 2019. Success was defined as IOP >5 and ≤21 mm Hg with IOP reduction ≥20% from baseline, without any retreatment and visual acuity better than negative light perception. MP-TSCPC retreatment was early and late, before and after 6 months postoperatively, respectively. Results: We included 94 eyes in 94 patients [mean (SD) age: 67.2 (13.4) y; 47.9% women]. The mean preoperative IOP was 24.9 (7.1) mm Hg and was reduced to 18.9 (6.3) at month 6 ( P <0.0001). The success rate decreased progressively over time and reached 45.5% at 6 months. Patients with 6-month surgical success had lower mean axial length than others [24.1 (1.5) vs. 25.5 (2.1) mm, P =0.05]. In patients with early and late MP-TSCPC retreatment, the 6-month success rate was 16.7% and 63.6%, respectively. Conclusions: MP-TSCPC performed with a 120-second setting reduced IOP, with 45.5% success at month 6 and few complications. Axial length was newly described as affecting success, probably linked to the ciliary-body position. Retreatment seemed to be of little benefit in nonresponders or those with early failure. Further studies on laser settings and ciliary-body location are required to find the best risk-benefit protocol.